G206(P) Recognising the risk factors: missed opportunities to prevent rickets. (27th April 2015) - Hutchings, FA; Oliver, N; Thursby-Pelham, A; Burren, CP
Abstract : Aim: Implementing the NICE guidance published in November 2014 for vitamin D supplementation of at-risk groups, including all children under-five years of age, would help reduce childhood rickets due to Vitamin D deficiency. Whilst awareness of Vitamin D is increasing, we often assume that UK infants have sufficient calcium dietary intake. This case series highlights rickets arising when insufficient dietary calcium compounds the effects of insufficient Vitamin D. Methods: We reviewed case-notes, biochemical and radiological data of four children diagnosed with rickets at our hospital during the past 18 months. Results: One child presented aged seven months with seizures. She had a prolonged corrected QT interval secondary to profound hypocalcaemia (corrected calcium 1.49 mmol/L), and vitamin D Deficiency (vitamin D <6 nmol/L). The remaining three infants (aged 16–20 months) presented with bony deformities characteristic of rickets, and Vitamin D supplementation had recently been commenced in primary care. Total Vitamin D levels were 26.3, 38.9 and 51.1 nmol/L each with a significant proportion of the total Vitamin D as D2 consistent with supplementation. These three cases had normo-calcaemia (2.3–2.54 mmol/L). Radiology showed rachitic changes. All cases had pigmented skin, were predominantly breastfed and had no vitamin D supplementation during the first year of life. The clinical and radiological rachitic changes were more marked than expected for the levels of Vitamin D. All were cow's milk allergic (confirmed on specific IgE testing) and were slow to wean, with prolonged breast feeding. The children had inadvertently been on low calcium diets without supplementation. All children have made good progress with subsequent appropriate calcium and vitamin D supplementation. Conclusion: This series illustrates commonly recognised risk factors for rickets, namely skin pigmentation, exclusive and prolonged breastfeeding, and the lack of Vitamin D supplementation. Undoubtedly the lack of vitamin D was contributory to the development of rickets and appropriate supplementation could have minimised the adverse skeletal effects. These cases also highlight that a calcium-deplete diet is an additive risk factor for the development of rickets. Infants with cow's milk protein allergy comprise a clinical group in whom it is important to consider the need for calcium supplementation alongside Vitamin D.